Collagenase injection versus limited fasciectomy surgery to treat Dupuytren’s contracture in adult patients in the UK: DISC, a non-inferiority RCT and economic evaluation - Joseph Dias; Puvan Tharmanathan; Catherine Arundel; Charlie Welch; Qi Wu; Paul Leighton; Maria Armaou; Belen Corbacho; Nick Johnson; Sophie James; John Cooke; Christopher Bainbridge; et al. (Health Technology Assessment)
Background Dupuytren’s contracture is caused by nodules and cords which pull the fingers towards the palm of the hand. Treatments include limited fasciectomy surgery, collagenase injection and needle fasciotomy. There is limited evidence comparing limited fasciectomy with collagenase injection. Objectives To compare whether collagenase injection is not inferior to limited fasciectomy when treating Dupuytren’s contracture. Design Pragmatic, two-arm, unblinded, randomised controlled non-inferiority trial with a cost-effectiveness evaluation and nested qualitative and photographic substudies. Setting Thirty-one National Health Service hospitals in England and Scotland. Participants Patients with Dupuytren’s contracture of ≥ 30 degrees who had not received previous treatment in the same digit. Interventions Collagenase injection with manipulation 1–7 days later was compared with limited fasciectomy. Main outcome measures The primary outcome was the Patient Evaluation Measure score, with 1 year after treatment serving as the primary end point. A difference of 6 points in the primary end point was used as the non-inferiority margin. Secondary outcomes included: Unité Rhumatologique des Affections de la Main scale; Michigan Hand Outcomes Questionnaire; recurrence; extension deficit and total active movement; further care/re-intervention; complications; quality-adjusted life-year; resource use; and time to function recovery. Randomisation and blinding Online central randomisation, stratified by the most affected joint, and with variable block sizes allocates participants 1 : 1 to collagenase or limited fasciectomy. Participants and clinicians were not blind to treatment allocation. Results Between 31 July 2017 and 28 September 2021, 672 participants were recruited (n = 336 per group), of which 599 participants contributed to the primary outcome analysis (n = 285 limited fasciectomy; n = 314 collagenase). At 1 year (primary end point) there was little evidence to support rejection of the hypothesis that collagenase is inferior to limited fasciectomy. The difference in Patient Evaluation Measure score at 1 year was 5.95 (95% confidence interval 3.12 to 8.77; p = 0.49), increasing to 7.18 (95% confidence interval 4.18 to 10.88) at 2 years. The collagenase group had more complications (n = 267, 0.82 per participant) than the limited fasciectomy group (n = 177, 0.60 per participant), but limited fasciectomy participants had a greater proportion of ‘moderate’/‘severe’ complications (5% vs. 2%). At least 54 participants (15.7%) had contracture recurrence and there was weak evidence suggesting that collagenase participants recurred more often than limited fasciectomy participants (odds ratio 1.39, 95% confidence interval 0.74 to 2.63). At 1 year, collagenase had an insignificantly worse quality-adjusted life-year gain (−0.003, 95% confidence interval −0.006 to 0.0004) and a significant cost saving (−£1090, 95% confidence interval −£1139 to −£1042) than limited fasciectomy with the probability of collagenase being cost-effective exceeding 99% at willingness to pay thresholds of £20,000–£30,000 per quality-adjusted life-year. At 2 years, collagenase was both significantly less effective (−0.048, 95% confidence interval −0.055 to −0.040) and less costly (−£1212, 95% confidence interval −£1276 to −£1147). The probability of collagenase being cost-effective was 72% at the £20,000 threshold but limited fasciectomy became the optimal treatment at thresholds over £25,488. The Markov model found the probability of collagenase being cost-effective at the lifetime horizon dropped below 22% at thresholds over £20,000. Semistructured qualitative interviews found that those treated with collagenase considered the outcome to be acceptable, though not perfect. The photography substudy found poor agreement between goniometry and both participant and clinician taken photographs, even after accounting for systematic differences from each method. Limitations Impacts of the COVID-19 pandemic resulted in longer waits for Dupuytren’s contracture treatment, meaning some participants could not be followed up for 2 years. This resulted in potential underestimation of Dupuytren’s contracture recurrence and/or re-intervention rates, which may particularly have impacted the clinical effectiveness and long-term Markov model findings. Conclusions Among adults with Dupuytren’s contracture, collagenase delivered in an outpatient setting is less effective but more cost-saving than limited fasciectomy. Further research is required to establish the longer-term implications of both treatments. Future work Recurrence and re-intervention usually occur after 1 year, and therefore follow-up to 5 years or more could resolve whether the differences observed in the Dupuytren’s interventions surgery versus collagenase trial to 2 years worsen. Study registration Current Controlled Trials ISRCTN18254597. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme (NIHR award ref: 15/102/04) and is published in full in Health Technology Assessment; Vol. 28, No. 78. See the NIHR Funding and Awards website for further award information. Plain language summary Dupuytren’s contracture happens when fibrous tissue builds up and over time bends the finger(s) into the palm, causing problems with hand function. To treat this, surgery is usually used to straighten the finger. A less intrusive alternative is an injection (collagenase), which softens the tissue after which the finger is moved to straighten it. The Dupuytren's interventions surgery versus collagenase trial recruited 672 patients who were equally and randomly assigned to have either surgery or collagenase injection. The study assessed whether the injection was as good and as safe as surgery at straightening the finger and how long the finger remained straightened. For up to 2 years after treatment, the participant’s hand function and general health were assessed. Some participants provided photographs to monitor changes to the finger, and some were asked about their experiences of Dupuytren’s contracture and treatments. We found: Hand health improved following both treatments. Initially, the injection treatment improved hand health more than surgery. However, by 1 year, surgery improved hand health more than the injection treatment. Recovery of hand function was quicker for participants who received the injection; however, they were more likely to need further treatment (i.e. further care and/or re-intervention). Participants said that the less positive longer-term outcome was acceptable for a better treatment experience. For both treatments, interviews found that participants were happy with the hand improvement they experienced at 3 months after treatment. More than half of participants had no complications, moderate or severe complications were rare, and participants who had surgery had more of these. The injection was cheaper but less effective than surgery at 1 year and was considered good value for money. However, by 2 years surgery became the better option due to its greater improvement in health benefits. Participant-taken photographs can help monitor Dupuytren’s contracture but do not give the same results as measurements taken in a clinic. Scientific summary Background Dupuytren’s disease affects over 2 million UK adults. Cords pull the fingers down towards the palm. This interferes with hand function and dexterity, impacting on quality of life. Current treatments to remove, dissolve or break the cords include surgical correction [limited fasciectomy (LF)], collagenase injection (an enzyme injected into the cord), and percutaneous needle fasciotomy (a needle is used to puncture, weaken and cut the cord). None of these treatments cure the tendency to develop Dupuytren’s contracture (DC) and so the cords and contracture can recur over time. Collagenase has some benefits over LF surgery including shorter recovery and no dependence on operating theatre availability for delivery of the intervention. There is, however, limited robust evidence comparing surgical correction and collagenase injection in terms of clinical effectiveness, cost-effectiveness, and in terms of patient’s experiences and preferences. Objectives The primary objective was to compare whether collagenase injection is not inferior to LF in the treatment of DC. Secondary objectives included investigation of recurrence at 1 and 2 years after treatment and cost-effectiveness. A qualitative substudy explored patients’ views of collagenase and LF, and a photography substudy investigated whether measurements of extension and flexion made on photographs taken by patients reflect goniometric measurements to assess recurrence. Methods Design The Dupytren's interventions surgery vs collagenase (DISC) trial was a multicentre, pragmatic, parallel two-arm randomised controlled non-inferiority trial with a cost-effectiveness evaluation, and nested qualitative and photography substudies. Participants were randomised on an equal basis to receive either of the two treatment options via a remote randomisation service. Randomisation was blocked, with randomly varying block sizes, and stratified by reference (worst-affected) joint [metacarpophalangeal (MCP) joint or proximal interphalangeal (PIP) joint]. Participants were followed up at 3 months, 6 months, 1 year and 2 years after treatment. Data collection included joint measurements and photography at baseline, and all follow-up time points. Setting Trial recruitment was undertaken in 31 NHS hand units across England and Scotland between June 2017 and September 2021. Participants Patients aged 18 years and over with a discrete, palpable Dupuytren’s cord causing contracture of ≥ 30 degrees and who were appropriate for both study treatments, were eligible for inclusion. Patients were excluded if they had severe contractures (> 135 degrees); had received treatment to the study digit; had other pre-existing disorders affecting hand function; had contraindications to collagenase; had a coagulation disorder; were female and pregnant or breastfeeding; had participated in a study involving another investigational medicinal product within 12 weeks or had another disease or disorder which would put them at risk if participating. Interventions The intervention was collagenase Clostridium histolyticum injection, supplied through routine NHS stocks. Collagenase was injected as three aliquots at set anatomical points in line with the current approved summary of product characteristics. After an interval of 1–7 days, participants returned to the clinic, where under local anaesthetic the cord was snapped to correct the contracture. The control group received LF surgery to remove the diseased nodules and cord to correct the contracture. Participants were followed up at routine wound check appointments following intervention. Outcomes The primary outcome was the Patient Evaluation Measure (PEM) score (0–100 with higher scores indicating worse outcome) at 1 year after treatment. The PEM was also completed at 3 months, 6 months and 2 years after treatment. Secondary outcomes included the Unité Rhumatologique des Affections de la Main (URAM) scale, Michigan Hand Outcomes Questionnaire (MHQ), recurrence, extension deficit and total active movement, complications, further treatments (including further care and/or re-intervention), health-related quality of life [EuroQol-5 Dimensions, five-level version (EQ-5D-5L)], resource use, time to recovery of function (using a single assessment numeric evaluation measure) and overall hand assessment. All outcomes were collected at 3 months, 6 months, 1 year and 2 years. The PEM was also recollected immediately prior to treatment delivery, and the time to recover function and quality of life were also collected at 2 and 6 weeks after treatment. Outcomes were collected primarily in hospital clinics, with some participants being followed up for postal, telephone, or video data collection during the COVID-19 pandemic. The qualitative substudy explored participants experiences of DC and treatments. The photography substudy explored the agreement between measurements obtained using a goniometer and photographs taken by participants at home, to determine whether the two methods of measurement might feasibly be used interchangeably. Results Clinical effectiveness In total 672 participants (64.6%) were recruited and randomised; 336 to receive collagenase injection and 336 to receive LF. Baseline characteristics were similar across groups. Of the 672 randomised participants, 621 (92.4%) received treatment as part of the trial. Cross-over was limited: one participant (0.3%) allocated to collagenase received LF; seven participants allocated to LF received collagenase (2.1%). On average participants received collagenase by 12.1 weeks [standard deviation (SD) 13.7] and LF in 17.7 weeks (SD 16.5) after randomisation. Most participants (n = 315, 95.2%) had just one digit treated. No participants required an unplanned inpatient admission following treatment and 62.0% (n = 201) collagenase participants and 78.3% (n = 224) LF participants had full correction following treatment. At 1 year (primary time-point) the difference in PEM scores showed that collagenase was inferior to LF; difference 5.95 [95% confidence interval (CI) 3.12 to 8.77; p = 0.49]. The benefit of LF over collagenase continued to increase to 2 years (7.18, 95% CI 4.18 to 10.88; p = 0.82). There were no material changes in these results for any of the sensitivity or additional analyses undertaken. The primary analysis therefore shows that there is little evidence to support rejection of the hypothesis that collagenase is inferior to LF at 1 and 2 years post treatment. Indeed, the observed data are highly compatible with LF being superior to collagenase with regard to the primary outcome measure at both these time points. Patient Evaluation Measure overall assessment scores corresponded with the primary outcome analyses and participants in both groups reported positive experiences of treatment. The estimated difference in URAM scores followed those of PEM, increasing in favour of LF over time from 3 months (0.82, 95% CI −0.21 to 1.84; p = 0.12) to 5.37 (95% CI 3.85 to 6.88; p ≤ 0.00005) at 2 years. At 1 year MHQ scores were higher (better) in the LF group (1 year: −4.69, 95% CI −7.27 to −2.12; p = 0.0004) and this continued at 2 years (2 years: −6.71, 95% CI −9.60 to −3.82; p ≤ 0.00005). Return to function was better in the short term for the collagenase group (week 2: 14.93, 95% CI 11.66 to 18.19; p ≤ 0.00005; 6 weeks: 5.00, 95% CI 2.29 to 7.70; p = 0.003) but by 1 year function was superior after LF (−4.93, 95% CI −7.63 to −2.22; p = 0.0004). At 1 year participants who received LF were more likely to respond as being ‘cured’ or ‘much better’ than participants who received collagenase [odds ratio (OR) 3.01, 95% 2.15 to 4.23; p ≤ 0.00005]. Passive extension deficit was similar between the groups at baseline (mean: 45.8°; SD 17.0). Following collagenase treatment, extension deficit seemed to be worse at all time points ranging from a difference of 5.73° (95% CI 2.88 to 8.59; p = 0.0001) at 3 months to 10.10° (95% CI 6.46 to 13.73; p ≤ 0.00005) at 1 year and increasing again up to 2 years. Results when imputed data were included were similar. Increases in reference joint passive range of movement (RoM) were similar between the two groups following treatment. However, from 6 months there was strong evidence that collagenase resulted in poorer passive RoM (−7.42°, 95% CI −11.54 to −3.29; p = 0.0004) and this difference increased further over time. Measurements of active extension deficit were similar between the two groups at baseline (mean: 51.9°, SD 16.1). Like passive extension deficit, active extension deficit was worse following collagenase treatment at all time points, ranging from a difference at 3 months of 5.57° (95% CI 3.02 to 8.12; p ≤ 0.00005) to 11.52° (95% CI 8.13 to 14.91; p < 0.00005) at 1 year and increasing again up to 2 years. Results when imputed data were included were similar. Increases in active RoM of the reference joint were similar between the two groups following treatment. However, from 6 months there was strong evidence that collagenase resulted in poorer active RoM (−8.37°, 95% CI −11.99 to −4.75; p ≤ 0.00005). Again, this difference increased further over time. In total 54 participants (15.7%) experienced recurrence of DC. There was weak evidence to suggest that following collagenase treatment participants were more likely to experience recurrence compared to participants who received LF (OR 1.39, 95% CI 0.74 to 2.63; p = 0.31). There were 267 complications (0.82 per participant) reported for the collagenase group, compared to 177 complications (0.60 per participant) reported for the LF group. Participants in the LF group experienced a higher proportion of ‘moderate’ or ‘severe’ complications (5% vs. 2%). In the first year following intervention, most participants did not require re-intervention (n = 399, 64.3%), which dropped to 47.7% by 2 years. By 2 years, 10% of collagenase participants had re-intervention compared to 2.5% of LF participants. Cost-effectiveness The mean cost of surgery was estimated to be £2510 (SD £818) per participant compared to £1008 (SD £94) for the collagenase group. The overall mean healthcare cost was slightly lower in the collagenase group compared to the LF group at 2 years (mean difference: −£28, 95% CI −£87 to £30). Baseline utility scores (EQ-5D-5L) were slightly higher in the LF group (mean 0.794, SD 0.170) compared to the collagenase group (mean 0.791, SD 0.174), but this was not statistically significant (95% CI −0.029 to 0.024). For both groups, utility scores decreased immediately following treatment but by 3 months had reverted to baseline levels. The mean difference between groups at 2 years was −0.044 (95% CI −0.077 to −0.010). After adjustment for baseline costs and utilities, participants who received collagenase showed a statistically insignificant decrease in quality-adjusted life-year (QALY) gains at 1 year (−0.003, 95% CI −0.006 to 0.0004) and a reduced cost (−£1090, 95% CI −£1139 to −£1042) compared to LF participants. The probability of collagenase being cost-effective was over 99% for both willingness-to-pay thresholds of £20,000 and £30,000 per QALY at 1 year and this finding was robust for the sensitivity analyses conducted. At 2 years collagenase continued to be both significantly less costly (−£1212, 95% CI −£1276 to −£1147) and less effective (−0.048, 95% CI −0.055 to −0.040). The probability of collagenase being cost-effective was 72% at the £20,000 threshold and 37% at the £30,000 threshold. The longer-term Markov model indicated that collagenase became less cost-effective than LF at the lifetime horizon, the probability of collagenase being cost-effective ranged from 22% to 16%. Qualitative Semistructured qualitative interviews were conducted with 45 patients, resulting in four core topics: Lived experience; knowledge; experience; and looking to the future. Participants reported living for extended periods with DC and seeking medical advice only when impacted by the difficulty in doing tasks or appearance of the hand. Most participants reported improvement in their contracture and function; some treated with collagenase noted that while the outcome was not perfect, it was acceptable. More participants treated with collagenase reported preferring this in the future compared to LF participants preferring the same intervention again. Photography substudy The difference between goniometric measurements and participant-taken photographs for active extension deficit was −9.7° (SD 16.2) for MCP, 8.0° (SD 15.1) for PIP and 5° (SD 9.5) for distal interphalangeal (DIP) joints. The limits of agreement were approximately ± 30° for MCP from ± 12° to ± 30° for PIP and ± 18° for DIP joints. For flexion, differences were −0.8° (SD 19.3) for MCP, −1.6° (SD 14.5) for PIP and −2.7° (SD 13.5) for DIP joints. Limits of agreement were approximately ± 36° for MCP, ± 20° for PIP, and a range of ± 33° to ± 24° for DIP joints. Conclusions In adults with moderate DC, collagenase, when delivered in an outpatient setting, proves to be significantly cost-saving compared to LF throughout the trial. While collagenase demonstrates comparable QALY gains to LF at 1 year, its effectiveness is significantly lower at 2 years. This leads to a changing cost-effectiveness profile over time, with collagenase being highly likely cost-effective at 1 year. However, the probability of its cost-effectiveness declines at 2 years. The Markov model results indicate that the likelihood of collagenase being considered cost-effective compared to LF at the lifetime horizon falls below 22% at thresholds of £20,000/QALY and above. The DISC trial followed participants for up to 2 years after treatment and therefore further research is required to better understand the longer-term trajectories for patients following initial contracture correction. Implications for health care The results from the DISC trial provide strong indicators for the planning of care of DC patients in the UK. The comprehensive nature of the clinical and cost-effectiveness data provides the opportunity for the UK National Institute for Health and Care Excellence to update its recommendation on the treatment options for DC. Of relevance will be how to situate the use of collagenase if it is reintroduced for use in the NHS. The role of primary care services in ensuring timely first diagnosis and referral of patients with DC needs to be strengthened. The results of the DISC trial provide a basis to engage further with primary care providers in relation to this. The DISC photography substudy provides an indication of how patient-taken photographs can complement clinic measurements if processes are streamlined further. Further investigation will be key in establishing remote assessment and follow-up for DC patients but noting that clinic measurements remain necessary for final decisions on required care. Recommendations for future research Follow-up to 5 years or more would establish the evolution of differences observed at 2 years, particularly in relation to recurrence and re-intervention, which usually occurs after 1 year. Also, the data collection in the DISC trial has been used as the basis for planning the data collection for the ongoing HAND-2 trial [NIHR: 127393; ISRCTN: 18254597], which will allow for a network meta-analysis of all key interventions for DC. The results from the qualitative substudy provide direction on planning further research to understand behavioural trends that influence a patient’s decision to seek care and return to care after initial intervention. Study registration Current Controlled Trials ISRCTN18254597. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme (NIHR award ref: 15/102/04) and is published in full in Health Technology Assessment; Vol. 28, No. 78. See the NIHR Funding and Awards website for further award information.